The Role of Interpals Application in Developing Intercultural Communication Competence among Learners in Jakarta - Dara Dwi Kencana; Arjulayana Arjulayana; Moh.Iqbal Firdaus (Lembaran Ilmu Kependidikan, 2026)
This study investigates the role of the Interpals application in fostering intercultural communication competence (ICC) among learners in Jakarta. A qualitative approach was employed, utilizing interviews and chat based observations as primary data sources. The participants included 25 learners who actively engaged in intercultural interactions through the Interpals platform. The findings indicate that participation in Interpals facilitates the development of ICC through direct and meaningful intercultural communication. The participants exhibited positive attitudinal changes, including increased openness and curiosity toward different cultures, along with enhanced cultural understanding gained from exchanging information and personal experiences. Furthermore, improvements were observed in their communication skills, particularly in clarifying meaning, adjusting language use, and minimizing misunderstandings. In addition, the study identified the development of internal outcomes, such as empathy and cultural awareness, as well as external outcomes reflected in the ability to communicate appropriately and effectively in intercultural contexts. Overall, the findings suggest that Interpals functions as a valuable digital platform that supports experiential learning and promotes the development of intercultural communication competence in the digital era.